2004
DOI: 10.1097/00008483-200401000-00006
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Training Responses Using Self-regulation in a Residential Rehabilitation Program

Abstract: The training response was similar between the three methods used to monitor exercise intensity. Thus, patients are able to gauge their own exercise intensity reasonably when instructed to exercise at a perceived exertion of 13. This suggests that close heart rate monitoring may not always be necessary for many stable patients with cardiovascular disease to achieve the benefits of a rehabilitation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
1
32
0
4
Order By: Relevance
“…In addition, the benefit of using technology over manual methods is yet to be conclusively proven for patients who are not considered to be high risk. Over the course of one month, home rehabilitation participants increased their exercise capacity and were able to regulate their own physical exertion at comparable rates regardless of whether they were using self-assessment (Borg scale) or technological measurements [19]. In the long term, there is evidence to suggest that those who continue to self-monitor maintain change for longer than those who do not [2,20].…”
Section: Technology Use In Cardiac Rehabilitationmentioning
confidence: 99%
“…In addition, the benefit of using technology over manual methods is yet to be conclusively proven for patients who are not considered to be high risk. Over the course of one month, home rehabilitation participants increased their exercise capacity and were able to regulate their own physical exertion at comparable rates regardless of whether they were using self-assessment (Borg scale) or technological measurements [19]. In the long term, there is evidence to suggest that those who continue to self-monitor maintain change for longer than those who do not [2,20].…”
Section: Technology Use In Cardiac Rehabilitationmentioning
confidence: 99%
“…A preliminary randomized controlled study (Ilarraza, Myers, Kottman, Rickli, & Dubach, 2004) observed patients after myocardial infarction or bypass surgery who determined their training intensity completely by themselves using the rating of perceived exertion ("slightly strenuous"). At the same amount of training (5 × 30 min cycle ergometer per week plus 2 × 45 min walking per day), they improved their aerobic capacity within 30 days by approximately the same mean rate (+23%) as did patients who regulated their training intensity using heart rate reserve (70% HRR: +34%) or both HRR and perceived exertion (60-80% of HRR and "slightly strenuous": +31%; Ilarraza et al, 2004).…”
Section: Optimization Of Health Effectsmentioning
confidence: 99%
“…The latter usually have to be instructed, guided, and coached more intensely. Apart from studies with very small samples, in which no side effects were observed during self-regulated exercise (Ilarraza et al, 2004), it is unclear how far self-regulation alters the risk for side effects. Both increased as well as decreased risk seems plausible, depending on the control competency and the respective conditions.…”
Section: Side Effects and Potential Of Self-regulated Exercise Trainimentioning
confidence: 99%
“…Werden sie eingehalten, ist das Training effektiv und der Patient wird nicht durch eine zu hohe Belastung gefährdet. Die Borg-Skala wurde auch bei Patienten mit Herzerkrankungen mit Erfolg bei der Sporttherapie eingesetzt [25].…”
Section: Aerobes Ausdauertrainingunclassified